علاج كسور بين المدورين غير الثابتة - يوسف صفوان; جوني أحمد; متكلم محمد علي (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة(30) مريضاً راجعوا مشفى الأسد الجامعي باللاذقية لديهم كسر بين المدورين غير ثابت وذلك في الفترة الواقعة ما بين عامي (2005 – 2010). كان معدل إصابة الذكور أقل من معدل إصابة الإناث ( 14ذكراً و16 أنثى) مع ذروة الحدوث في عمر (64.76). درست النتائج الوظيفية للعلاج الجراحي باستخدام DHS وتبديل المفصل البدئي و غيرها كما يلي: أستخدم DHS في (16) حالة وتبديل مفصل بدئي في (11) حالة وغيرها في (3) حالات وتمت متابعة المرضى بعد العمل الجراحي لمدة لا تقل عن ستة أشهر وتم تقييم النتائج الوظيفية للعلاج وفق مقياس Haris للحوض. كانت نتائج العلاج بتبديل المفصل البدئي أفضل من باقي الطرق حيث أعطى نتائج ممتازة بنسبة (27.2%) مقابل (0%) لاستخدام DHS و (0%) لغيرها . أما من حيث المضاعفات فكان العلاج الجراحي قليل المضاعفات بتبديل المفصل البدئي حيث أعطى نتائج سيئة في (9.9%) من المرضى مقابل (50% ) للعلاج DHS و (33.3%) لغيرها. This study includes 30 cases of unstable intertrochanteric fractures treated in AL-ASSAD University Hospital between 2005 and 2010. The average number of males is less than females (14 males and 16 females). The mean average age is 64.76 years old. We have evaluated the functional results of these cases which have been treated by primary Bipolar arthroplasty compared to internal fixation using DHS and other internal fixations. We have used DHS in 16 cases and prosthetic joint in 11 cases and the 3 others cases were treated by other methods. The results of primary arthroplasty were excellent in 27.2% of cases compared to DHS 0% and other methods 0% good in primary arthroplasty 55.5% compared to DHS 20% and the other methods 33%. There were poor functional results in primary arthroplasty 9.9% compared to DHS 50% and the other methods 33.3%. The primary arthroplasty, however, offers quick recovery and avoids the risks associated with internal fixation and enables the patient to maintain a good functional result after surgery.